Characterization of various blood and graft sources: a prospective series. Issue 9 (16th January 2013) - Chevallier, Patrice; Robillard, Nelly; Illiaquer, Marina; Esbelin, Julie; Mohty, Mohamad; Bodin‐Bressollette, Celine; Guillaume, Thierry; Stocco, Veronique; Auffray, Fabienne; Derenne, Sophie; Planche, Lucie; Bene, Marie‐Christine; et al.
<x xml:space="preserve">Abstract</x> Background Studies comparing cell components of blood and graft sources are very scarce. We present here a thorough study examining the cellular content of various sources of blood and cell therapy products. Study Design and Methods We have prospectively compared by fluorescence‐activated cell sorting analyses the cellular composition of three blood sources on the one hand—peripheral blood (PB; n = 10) versus granulocyte–colony‐stimulating factor (G‐CSF)‐mobilized PB (GCSF‐PB, n = 10) versus cord blood (CB, n = 10)—and of three graft sources on the other hand—unmanipulated bone marrow (uBM, n = 5) versus leukapheresis product (LP, n = 10) versus thawed CB graft (n = 7). Results All median absolute numbers of cell subsets were found significantly higher in GCSF‐PB and LP, except for monocytoid dendritic cells (mDCs) in CB and uBM. The most impressive results were the median quantities of memory T and B lymphocytes but also of plasmacytoid DCs (pDCs) contained in LP compared to thawed CB graft, with ratios of 375, 318, and 247, respectively. The proportions of naive and CD4+/CD8− T cells, transitional B cells, and CD5+ and naive B lymphocytes were found significantly higher in CB samples while the proportions of mDCs and pDCs were found significantly lower. Conclusion Our study shows strong differences in terms of quantitative and qualitative cellular composition between several blood or graft sources, possibly explaining the differences observed in terms of outcomes after transplant.